Di-tert-butyl N,N′-(octahydropentalene-2,5-diyl)dicarbamate - Kendhale, Amol M. (International Union of Crystallography, 2008)
In the molecule of the title compound, C(18)H(32)N(2)O(4), the central bicyclo[3.3.0]octane (octahydropentalene) has a rigid ring junction. Both rings of the bicyclo[3.3.0]octane unit adopt an envelope conformation, and the flexible tert-butylcarbamoyl side chains each have an extended conformation. Such a constrained bicyclo[3.3.0]octane aliphatic template is of interest with respect to the design of novel self-assembling motifs. Molecules related by c-glide symmetry are linked via intermolecular N—H⋯O hydrogen bonds, forming a two-dimensional layer structure. Neighboring layers are weakly associated along the a axis due to the close approach of the tert-butylcarbamoyl groups (2.55 Å).